Extensive families of constant region genes in a phylogenetically primitive vertebrate indicate an additional level of immunoglobulin complexity. - Kokubu, F (1987)
A homologous probe for the constant region of the Heterodontus francisci (horned shark) immunoglobulin heavy chain was used to screen a genomic DNA library constructed in bacteriophage lambda, and a large number of independent clones were recovered. Their hybridization patterns with segment-specific probes are consistent with the close linkage of heavy-chain constant (CH), joining (JH), and variable (VH) gene segments. Differences in the nucleotide sequences of the first CH exon of five genes primarily are localized to 5' positions; extended regions of sequence identity are noted at 3' positions. The predicted amino acid sequences of each gene are different and are related distantly to the corresponding regions of higher vertebrate immunoglobulins. Gene-specific oligodeoxynucleotide probes were used to establish that at least three of the five genes are transcriptionally active. Quantitative gene titration data are consistent with the large numbers of genes suggested by the library screening analyses. In this representative early vertebrate, it appears that (VH-diversity-JH) segments are associated with individual constant region genes that can differ at the predicted protein level.